Scientists have favorable opinions on immunity certificates but raise concerns regarding fairness and inequality - Iván Aranzales (Nature Portfolio, 2021)
Abstract During the first wave of the COVID-19 pandemic, we collected over 12,000 responses from a survey of scientists, who were asked to express their opinions on immunity certificates (also called “immunity passports”) as a potential instrument to lessen the impact of the crisis. Overall, we find that scientists perceive immunity certificates as favorable for public health (50.2%) and the state of the economy (54.4%) while one-fifth (19.1%) and one-sixth (15.4%) disagree. Scientists stipulate some concerns about fairness (36.5%) and inequality (22.4%) arising from implementation of immunity certification. We find some smaller differences among scientific fields, particularly between health scientists and social scientists, with the latter being slightly more positive about the effect of immunity certification. Scholars in the United States, including health scientists, are more likely to view the immunity certificates favorably and mention fewer concerns about this policy’s effect on fairness and inequality. Female scholars are significantly less in favor of immunity certificates, while scientists with more conservative political views hold more favorable opinions. Our results reveal that given the uncertainties during an early phase of a pandemic, scientists see scope for immunity certification to lessen the general societal impacts of the crisis.